2013
DOI: 10.1007/s40261-013-0104-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Prescription Patterns Among Patients Diagnosed With Depressive Disorder Based on Claims Database in Japan

Abstract: Based on analysis of prescription patterns and type of treatment used for treating non-psychotic major depression, a majority of patients were not treated according to the recommended guidelines in Japan. Various patterns of prescription and use of polypharmacy were observed over time. The median duration of treatment was shorter than the recommendation (6 months) in the guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
3
24
1
Order By: Relevance
“…Hiroshige Fujishiro, MD, PhD, 21,22 Toshinori Nakamura, MD, 15 Kentaro Mizuno, MD, 23 Takahiko Inagaki, MD, 24,25 Eiichi Katsumoto, MD, 26 Hiroaki Tomita, MD, PhD, 27 Kazutaka Ohi, MD, PhD, 28 Hiroyuki Muraoka, MD, PhD, 29 Kiyokazu Atake, MD, PhD, 12 Hitoshi Iida, MD, 30 Tatsuya Nagasawa, MD, PhD, 28 Junichi Fujita, MD, PhD, 31 Satoshi Yamamura, MD, 32 Toshiaki Onitsuka, MD, PhD, 33 Atsunobu Murata, MS, 34 Yoichiro Takayanagi, MD, PhD, 35 Hokuto Noda, MD, 36 Yukiko Matsumura, MD, 37 Kenji Takezawa, MD, PhD, 38 Jun-ichi Iga, MD, PhD, 39 Kayo Ichihashi, MD, 40 Kazuyoshi Ogasawara, MD, PhD, 21,41 Hisashi Yamada, MD, PhD, 4,42 Ken Inada, MD, PhD 29 and Ryota Hashimoto, MD, PhD 4,43 * Aim: Although treatment guidelines for pharmacological therapy for schizophrenia and major depressive disorder have been issued by the Japanese Societies of Neuropsychopharmacology and Mood Disorders, these guidelines have not been well applied by psychiatrists throughout the nation. To address this issue, we developed the 'Effectiveness of Guidelines for Dissemination and Education in Psychiatric Treatment (EGUIDE)' integrated education programs for psychiatrists to disseminate the clinical guidelines.…”
mentioning
confidence: 99%
“…Hiroshige Fujishiro, MD, PhD, 21,22 Toshinori Nakamura, MD, 15 Kentaro Mizuno, MD, 23 Takahiko Inagaki, MD, 24,25 Eiichi Katsumoto, MD, 26 Hiroaki Tomita, MD, PhD, 27 Kazutaka Ohi, MD, PhD, 28 Hiroyuki Muraoka, MD, PhD, 29 Kiyokazu Atake, MD, PhD, 12 Hitoshi Iida, MD, 30 Tatsuya Nagasawa, MD, PhD, 28 Junichi Fujita, MD, PhD, 31 Satoshi Yamamura, MD, 32 Toshiaki Onitsuka, MD, PhD, 33 Atsunobu Murata, MS, 34 Yoichiro Takayanagi, MD, PhD, 35 Hokuto Noda, MD, 36 Yukiko Matsumura, MD, 37 Kenji Takezawa, MD, PhD, 38 Jun-ichi Iga, MD, PhD, 39 Kayo Ichihashi, MD, 40 Kazuyoshi Ogasawara, MD, PhD, 21,41 Hisashi Yamada, MD, PhD, 4,42 Ken Inada, MD, PhD 29 and Ryota Hashimoto, MD, PhD 4,43 * Aim: Although treatment guidelines for pharmacological therapy for schizophrenia and major depressive disorder have been issued by the Japanese Societies of Neuropsychopharmacology and Mood Disorders, these guidelines have not been well applied by psychiatrists throughout the nation. To address this issue, we developed the 'Effectiveness of Guidelines for Dissemination and Education in Psychiatric Treatment (EGUIDE)' integrated education programs for psychiatrists to disseminate the clinical guidelines.…”
mentioning
confidence: 99%
“…Although pharmacotherapy guidelines recommend 6 months of antidepressant treatment for MDD, prescription patterns indicate that 68% of patients who start on antidepressant therapy stop after less than 6 months . A recent study from the Japanese health insurance database, which includes data on 600 000 patients, showed that more than half of the patients recently diagnosed with MDD received benzodiazepines, and that more than a quarter of these patients continued use for more than 1 month . Non‐pharmacotherapy guidelines recommend depression‐focused psychotherapy as an initial treatment for mild to moderate MDD, but only 28% of medical facilities in Japan claimed to be capable of conducting any kind of psychotherapy satisfactorily…”
mentioning
confidence: 99%
“…(49–54) report the seizure threshold (ST) in depressive patients who have undergone ECT, and found that ST was elevated when associated with benzodiazepine use, and thus determination of an adequate dose of stimulation is difficult in such cases. A recent study showed that a majority of depressive patients in Japan were not treated according to the treatment guidelines, and 58% of the depressive patients were treated by at least one benzodiazepine . Benzodiazepines are still overused in Japan, and this should be cautioned in clinical practice.…”
mentioning
confidence: 99%
“…Japan especially has a long history of the study of the relations between personality and depression, since the description of 'Immodithymia' by Mitsuzo Shimoda. 2 In this issue, Teraishi et al (3)(4)(5)(6)(7)(8)(9)(10)(11) discuss the role of personality as a trait marker of depression, whereas Chen et al (12-21) document the delayed onset of depression after traumatic stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation